An approach to improve the numerical simulation of crushed salt compaction behavior - Friedenberg, Larissa; Olivella, Sebastià (Frontiers in Built Environment, 2025)
Crushed salt as backfill material in a repository for high-level nuclear waste is aimed to act as a long-term barrier. The sealing effect of crushed salt evolves with ongoing compaction and therefore reduction in porosity and permeability. For a reliable prognosis of the compaction behavior in the long-term, constitutive models are crucial that capture the experimentally observed processes and credibly extrapolate these processes outside the range they were calibrated in. Up to now there is still no constitutive model for crushed salt which is validated against all factors/processes influencing compaction and/or the whole porosity range (especially φ < 5%). The constitutive model for crushed salt compaction available in CODE_BRIGHT has been used in the field of repository research for several years. It has been applied in recent research projects on crushed salt compaction, where shortcomings in the modelling of compaction behaviour in dependence on mean stress and deviatoric stress variations are identified. Based on this discovered potential for improvement an approach for the modification of the constitutive model is proposed within this paper. It addresses the assumption of an idealized geometry and network of grains which is introduced by mathematically constraint functions dependent on void ratio. The proposed approach aims to give more flexibility in the handling of geometry dependence. The paper comprises an introduction into the use of crushed salt in the context of nuclear waste repository. The description of the constitutive model for crushed salt available in CODE_BRIGHT is given, as well as, the proposal for improvement and its application. It is finished with a sensitivity study for the new approach followed by a summary and outlook.